In House Training Implementation of the Independent Curriculum based Tatanen in Bale Atikan at UPTD SD Negeri Salem, Pondoksalam - Imam Tabroni; Fitriani Nasihah (Indonesian Journal of Society Development, 2022)
Regent Regulation Number 103 of 2021 concerning TDBA and Regional Regulation Number 09 of 2021 concerning the Implementation of Education in Purwakarta Regency become the legal basis for the implementation of TdBA (Tatanen in Bale Atikan) in basic education. UPTD SD Negeri Salem which is used as a TdBA model school at the Pondoksalam Subdistrict level recently conducted an In House Training on the implementation of an independent curriculum based tatanen in Bale Atikan. IHT will be held for 3 days from 6-8 December 2022. This research uses a PAR (Participatory Action Research) approach, where researchers are part of the activities carried out and are practical. This IHT was attended by all school residents who aimed to provide a theoretical and practical understanding of Tatanen in Bale Atikan. The material presented on the first day was about the basic concepts of TdBA, the second day was about learning design, and the third day was about permaculture-based environmental management techniques